Knowledge among pregnant women regarding pregnancy-induced hypertension at a public hospital in Malaysia - Khuan, Lee; Mohd Zulkifli, Nik Qatrun Nadira; Abdul Rashid, Nor’ain; Mohammed, Auwalu (Asia Pacific Higher Learning, 2023)
Background: Pregnancy Induced Hypertension (PIH) is a significant contributor to various pregnancy complications. Therefore, an effective way to avoid possible fatal complications of the disease is to create awareness among pregnant women. Pregnant women who are aware of the danger signs of pregnancy will take responsibility for seeking medical attention if any complications arise. However, there is a lack of study done at public hospitals in Selangor regarding the knowledge level of PIH. Aim: To determine the level of knowledge regarding PIH among pregnant mothers. Methods: A cross-sectional design with systematic sampling was used. A total of 283 pregnant mothers who attended the antenatal clinic were recruited. All data were analysed using the Statistical Analysis Package for Social Sciences (SPSS) version 20. Results: The results showed that only 32.9% of the respondents had good knowledge of PIH, while 67.1% had poor knowledge regarding PIH. Most of them had a higher level of education, such as tertiary (62.9%), two-thirds were employed (68.2%), the majority were Malays (89.8%), had children between 2 and 4 years of age (36.4%), and 30.0% were currently pregnant for 16 to 20 weeks. Meanwhile, 53.0% of the respondents attended antenatal check-ups fewer than eight times. The result indicated a significant association between parity and level of knowledge on PIH (χ²= 7.848; p= 0.049). Conclusion: The majority of pregnant mothers have poor knowledge of PIH. Health education on PIH is needed to reduce the rate of delay in seeking treatment.